Trademarks Worth a Thousand Words : Freedom of Expression and the Use of the Trademarks of Others - Scassa, Teresa (Les Cahiers de droit)

(untitled) (Faculté de droit de l’Université Laval, 2012)
Trademarks play an important role in facilitating critical speech in an increasingly corporate capitalist society. Not only do they serve as markers for expressive content on the Internet, they can also be used as vehicles for the communication of critical messages about the trademark owner or its products or services. In this paper, the author examines the implicit balance in the Trade-marks Act between freedom of expression values and trademark rights, and argues that it is being significantly altered by the contemporary push for greater trademark protection. The author identifies specific problems that emerge from Canadian case law relating to freedom of expression and trademark law. These include the treatment by courts of intellectual property rights as private property rights, inattention to the trademark/copyright overlap, the troublesome distinction between commercial and non-commercial uses, and the phenomenon of trademark bullying. The author argues for a sharp evolution in Canadian case law that would establish clear parameters for critical speech using trademarks.